Endoscopic Thoracic sympathectomy for Primary Palmar hyperhidrosis - Chakradhar, Rupesh; Thapa, Amit (Nepal Journal of Neuroscience, 2020)
Primary hyperhidrosis is a disorder in which there is an excessive amount of sweating more than required for the body’s thermoregulation. It is due to excessive function of the sudomotor sweat control system in the absence of a sweating trigger.We had a 25-year-old engineer, who presented with complaints of profuse sweating in both his palms, feet and axillae for more than 10 years. He had distressing symptoms disabling his daily activities and causing negative impact in his social, professional, recreational and quality of life. He took medical treatments including topical agents, anticholinergics, iontophoresis and even botulinum toxin injection. All these not only failed to give relief but only aggravated his disappointment.Endoscopic thoracic bilateral sympathectomy was performed from T2 to T4 level. Drastic improvement was seen in immediate post-operative period. Pre-operative palmar temperature of 90° Fahrenheit increased to 96.5° Fahrenheit in immediate post-operative period. His post-operative period was uneventful and was discharged on the second postoperative day. On follow-up after 30 days, the patient was asymptomatic, fully satisfied with the surgery and without any complications.Endoscopic thoracic sympathectomy is a safe, effective, fast and minimally invasive surgical modality of treatment for primary hyperhidrosis.